SATISFACTION WHILE SHOPPING FOR ANOTHER PERSON: HOW OTHERS' PRODUCT EVALUATIONS INFLUENCE SHOPPER SATISFACTION. Issue 3 (3rd July 2018) - Gillison, Stephanie T.; Reynolds, Kristy E.
Abstract : This study looks at a common, but underresearched shopping situation: when the shopper is purchasing a product another person will use. This study uses expectancy disconfirmation theory to take into account multiple individuals' evaluations and (dis)confirmation judgments and illustrates how these judgments might impact one another. Using a series of four experiments, hypotheses are tested. Results show that a person's satisfaction with the shopping experience can be significantly impacted both positively and negatively by another person's product evaluation. Implications for theory and management are discussed and avenues for future research offered.